Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 7 - Rational Functions - 7.3 Multiplying and Dividing Rational Expressions - 7.3 Exercises - Page 580: 32


$= -\frac{4(n+6)}{(2n-3)}$

Work Step by Step

$\frac{2n+12}{4-3n} \div \frac{4n-6}{12n-16}$ $= \frac{2n+12}{4-3n} \times \frac{12n-16}{4n-6}$ $= \frac{2(n+6)}{4-3n} \times \frac{4(3n-4)}{2(2n-3)}$ $= \frac{2(n+6)}{4-3n} \times \frac{4(-(4-3n))}{2(2n-3)}$ $= \frac{2(n+6)}{1} \times \frac{-4}{2(2n-3)}$ $= -\frac{4(n+6)}{(2n-3)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.